Effects of Menstrual Cycle on Exercise Treadmill Parameters and Cardiac Troponin Release in Premenstrual Women - Aysu Oktay; Inanc Torustag; Ferruh Kemal Isman; Mehmet Agirbasli (Diagnostics, 2025)
Background: The diagnostic accuracy of the exercise treadmill test (ETT) remains suboptimal in premenopausal women. Menstrual cycle phases display hormonal variations and biological effects in premenopausal women. The early and late follicular phases of the menstrual cycle demonstrate nearly four-fold differences in estrogen levels. Methods: This study assessed the variability in ETT results between the early and late follicular phases in premenopausal women. This study included premenopausal females with regular menstrual cycles and chest pain. As per the study protocol, patients underwent two separate ETTs at the early and late follicular phases of the menstrual cycle. Hormones and high-sensitivity cardiac troponin T (hs-cTnT) were measured. The primary endpoint was the ST segment/heart rate (HR) index. The secondary endpoints were maximum ST/HR slope, ST segment depression, HR and blood pressure (BP) response, exercise capacity, and hs-cTnT change after ETT. Results: False-positive ETT results were common in premenopausal women. The early follicular phase displayed significantly higher hs-cTnT and BP responses to ETT compared to the late follicular phase. This study reports that ETT results are similar between the early and late follicular phases of the menstrual cycle in premenopausal women. Biological variability is observed in the BP and hs-cTnT response to ETT between the two phases. Conclusions: The menstrual cycle phase (early versus late follicular phase) did not affect the ETT results. The consideration of estrogen and hormonal status when evaluating the diagnostic test results can improve our understanding of cardiovascular disease in women.